PENERAPAN TERAPI MENGGAMBAR BEBAS TERHADAP PENURUNAN TANDA DAN GEJALA HALUSINASI PADA PASIEN SKIZOFRENIA DENGAN HALUSINASI DI RSJD DR. RM SOEDAJARWADI KLATEN PROVINSI JAWA TENGAH - Nur, Faizah; Susilowati, Tri; Reknoningsih, Wahyu (JURNAL KESEHATAN KARTIKA, 2023)
Background; Disturbance soul is problem mental health that can happen almost on residents throughout countries in the world. Amount client Schizophrenia at Home Sick Regional Soul Dr. RM. Soedjarwadi Province Central Java on four year final This Keep going experience increase . Based on background behind problem And the results obtained above , then writer interested For take action nursing about “ Implementation Therapy drawing free to decline sign symptom hallucinations on on patient schizophrenia with hallucinations at RSJD RM Dr. Soedjarwadi Klaten The problem that occurs most often in hospitals is hallucinations. Objective :  to determine the results of implementing the effectiveness of group activity therapy: Free drawing on reducing signs and symptoms of hallucinations. Method;  Study use design one group pretest posttest. Results application therapy draw free to decline sign And symptom hallucinations on respondent I experienced decline from a total of 9 results to 4 whereas respondent II experienced decline from 6 to 2. Results: Conclusion of this research is Therapy activity group Draw free can lower sign And symptom hallucinations on patient Hallucinations at RSJD Dr. RM. Soedjarwadi Klaten. Conclusion;  The researcher presents the results of this research as reference learning in addition material curriculum, as deep spiritual therapy control hallucinations , Expected writer furthermore before start implementation therapy , author do agreement with nurse in the room so it doesn't give action nursing care other than action therapy pharmacology And action taken writer.